Análise da aptidão física, postura e imagem corporal de escolares participantes de esportes individuais e coletivos - Schubert, Alexandre Caldeira (2011)
The purpose of the study was to analyze the physical fitness, posture and body image of students from both genders, practicing individual and team sports. The sample consisted of 367 children aged 8 to 16 years, 236 males and 131 females enrolled in public or private schools and attended of individual or collective sports, for a minimum period of one year. Physical fitness was assessed using the tests proposed by Silva and Gaya (2007), with flexibility, strength, abdominal strength, strength, upper limb strength, lower limb strength, agility, speed, endurance and body mass index. The Collin's protocol 1991 was used to assess body image and the protocol of Adams et al. (1985) for posture. Initially the data of anthropometric characteristics of sample were analyzed by Levene's test to determine equality of variances. Subsequently, the t test for independent samples was used to establish the comparison between genders. Than the data were categorized and used the Chi-square analysis to identify associations. The significance level was set at P <0.05. The results showed that most of the components of physical fitness from health or sports performance, when one advances in age the number of students who meet two criteria increases with the exception of flexibility and aerobic endurance. In relation to gender, we observed that a large number of students of both genders reach the criteria regardless of classification that is used in most of the components evaluated. The women showed up with higher assessed with the health criteria in all components of physical fitness, but in relation to sport performance, the girls have proportionately fewer evaluated that meet these criteria in relation to boys in agility and endurance. Team sports are shown with more proportional assessment given the criteria of sport performance for most components of physical fitness, while individual sports showed a higher number of evaluated following the criteria established in the physical fitness components focused on health. In relation to body image revealed a small advantage for those who were satisfied with their image than those who were dissatisfied, regardless of the classification that was used. Associations were found between the different components of physical fitness and other variables. The BMI was associated with all components of physical fitness and other variables. The results suggest that the practice of sports among students in the development phase can help in the improvement of some components of physical fitness and body image, but may not encourage much posture.